Postbiotic production: harnessing the power of microbial metabolites for health applications - Prajapati, Nidhi; Patel, Jinil; Singh, Sachidanand; Yadav, Virendra Kumar; Joshi, Chinmayi; Patani, Anil; Prajapati, Dharmendra; Sahoo, Dipak Kumar; Patel, Ashish (Frontiers in Microbiology, 2023)
Postbiotics, which are bioactive substances derived from the metabolic processes of beneficial microbes, have received considerable attention in the field of microbiome science in recent years, presenting a promising path for exploration and innovation. This comprehensive analysis looks into the multidimensional terrain of postbiotic production, including an extensive examination of diverse postbiotic classes, revealing their sophisticated mechanisms of action and highlighting future applications that might significantly affect human health. The authors thoroughly investigate the various mechanisms that support postbiotic production, ranging from conventional fermentation procedures to cutting-edge enzyme conversion and synthetic biology approaches. The review, as an acknowledgment of the field’s developing nature, not only highlights current achievements but also navigates through the problems inherent in postbiotic production. In order to successfully include postbiotics in therapeutic interventions and the production of functional food ingredients, emphasis is given to critical elements, including improving yields, bolstering stability, and assuring safety. The knowledge presented herein sheds light on the expanding field of postbiotics and their potential to revolutionize the development of novel therapeutics and functional food ingredients.